Comparison of Manufacturing Data Analysis For 5 & 3-Axis Vertical Machining Center for the Time and Tool Benefits of Industries - P. Sundar Singh Sivam, S.; Saravanan, K.; Pradeep, N.; Rajendra Kumar, S.; Karuppiah, Sathiyamoorthy (International Journal of Engineering and Technology, 2018)
The dawn of globalization of business and competitiveness in manufacturing has forced firms to enhance their manufacturing facilities to reply to plug necessities. One of the crucial factors for this is often machine evaluation that involves a crucial decision using general and obscure information. The Primarily mass production aims high productivity so as to reduce cost and interchangeability to facilitate simple assembly which necessitates the production devices to increase the speed of manufacture. Across the business, the assembly challenges pivot around cutting lead times, increasing throughout and obtaining products to market as quickly as possible alongside some less challenging problems like shorter runs, higher product combine, tighter tolerances, a lot of complicated geometries in harder materials, and complete machining during a single handling. Advancements in technology have resulted in a creation of a lot of responsive tools referred to as MTM systems that are computer numerical Control (CNC) systems capable of acting a variety of operations with multiple tools and spindles in a single setup. The following project aims at reduction of manufacturing cost by modifying the process layout and operational parameters by novel approach for an identical element for 3 and 5- Axis Vertical Machining center. Nowadays, machining layout and operational sequence plays a significant role in automotive business to produce products at competitive price in market which consists of Machines, Tools, fixtures, computer interface, trained professionals and form of products. MAKINO PS60 is a Multi axis CNC machine (BRIDGE PORT), that helps to perform the machining operations on the roles at 5 totally different axes to create the required profiles whose implementation can pave means for a few terribly important benefits like, seven machines are replaced by Single machine, Man power are reduced from 9 to 3 per day, Tools usage reduced from 40 to 30 per day & production cost can reduce up to 60%.Â Â